Effect of hand paddles on anaerobic energy release during supramaximal swimming - Ogita, F.; Onodera, T.; Izumi, T. (Medicine & Science in Sports & Exercise, 1999)
For supramaximal swimming, the effects of using hand paddles on maximal accumulated oxygen deficit, and aerobic and anaerobic energy release, were compared. Trained male college swimmers (N = 6) performed in a swimming flume. Water flow rate was set before each exercise so that exhaustion occurred in 30 s, 1 min, or 2-3 min. Water flow rates were significantly higher with paddles than with hands-alone. There were no differences between either condition for maximal accumulated oxygen deficit or accumulated oxygen uptake at any duration. Hand paddles produced faster swimming speeds without affecting metabolic factors when used in maximum-effort tasks. The value of experiencing an artificially high velocity that cannot be attained in a competitive no-paddle event has to be questioned. The use of paddles would appear to violate the principle of specificity because it associates unnatural movement patterns with maximal levels of metabolic output.